Diversity of Grasshopper on Agricultural Land and Savana in Dompu Regency, Indonesia - Khatimah, Ainul; Leksono, Amin Setyo; Yanuwiadi, Bagyo (Biotropika: Journal of Tropical Biology, 2022)
Grasshopper is one type of insect known as a plant pest that quite affects agricultural production. Grasshoppers also have benefits as natural predators and maintain ecological balance. One area where no research has been carried out on grasshopper diversity is Dompu Regency, West Nusa Tenggara, Indonesia. This research was conducted at 4 locations in Dompu, including corn, ex-corn, intercropping, and Doroncanga agricultural land, by making four transects at each location. Grasshoppers were collected using the insect net, and hand collecting was carried out at 07.00 and 16.00 WITA. The environmental factors that were calculated were air temperature, light intensity, wind speed, and air humidity, while the biotic factors observed were plant vegetation at each location and predators. Data analysis was performed using the Shannon-Wiener diversity index, evenness index, dominance index, and Margalef index. The results of this study indicate that Dompu Regency has the potential for diversity of grasshoppers with moderate criteria where the diversity of grasshoppers is strongly influenced by plant vegetation and human treatment on agricultural land.